Leisure in Art and Literature - Winnifrith, Tom. author. aut Link
XII, 159 p.
Keywords: The description or depiction of leisure activities has formed part of the subject matter of art and literature for a long time. This volume looks at funeral games in Homer, leisure as depicted in painting, and the part that literature played in promoting athleticism in public schools and Oxbridge.